Electrostatic chuck prepared by additive manufacturing and related methods and structures
Through additive manufacturing technology, inorganic composite materials and metal-based composite materials are used to directly form complex structures and channels of the electrostatic suction cup base, which solves the difficulties in material selection and processing processes in traditional manufacturing methods, realizes an efficient and low-cost manufacturing process, and improves product performance.
Patent Information
- Application Number
- CN202111648506.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-31
- Filing Date
- 2021-12-30
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2041-12-30
AI Technical Summary
In the prior art, when manufacturing the base of the electrostatic suction cup, there are difficulties in material selection and processing processes, resulting in high materials and processing costs, and a long manufacturing time.
Administrative manufacturing technology is adopted to form the base of the electrostatic suction cup through selective laser melting and other methods, and use inorganic composite materials and metal-based composite materials to directly form complex structures and channels, avoiding the complex steps of traditional mechanical processing and the high cost of vacuum brazing.
The high precision and complex structure of the base are achieved, reducing material and processing costs, shortening manufacturing time, and improving the thermal performance and flatness of the electrostatic suction cup.
Smart Images

Figure CN114695239B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure is in the field of a base assembly of an electrostatic chuck for supporting a workpiece during a step of machining the workpiece, wherein the base assembly ("base") is prepared by an additive manufacturing step. Background Art
[0002] Electrostatic chucks (also simply referred to as "chucks") are used in semiconductor and microelectronic device processing. The chuck holds a workpiece, such as a semiconductor wafer or a microelectronic device substrate, in position to perform processing on the surface of the workpiece. In particular, the electrostatic chuck supports and secures the workpiece at the upper surface of the chuck by generating an electrostatic attraction between the workpiece and the chuck. A voltage is applied to electrodes contained within the chuck to induce charges of opposite polarity in the workpiece and the chuck.
[0003] The chuck includes various structures, devices and designs that allow the chuck to perform or improve performance. A typical electrostatic chuck assembly is a multi-component structure that includes: a flat upper surface that supports the workpiece; electrical components such as electrodes, conductive coatings and ground connections that are used to control the electrostatic charge of the chuck and the supported workpiece; a temperature control system (such as a cooling system) that is used to control the temperature of the chuck and the supported workpiece; various other components that may include a measurement probe and a movable pin for supporting or changing the position of the workpiece relative to the chuck; and a temperature control media connection and an electrical connection that extends from the chuck to the tool interface.
[0004] A typical feature of an electrostatic chuck is a base that contains a temperature control system (e.g., a cooling system). The temperature control system includes a pattern of channels or passages formed inside the chuck that allow a fluid (e.g., a gas, water, or another liquid) to flow through the interior of the chuck to remove heat from the chuck and control the temperature of a supported workpiece during or after a processing step. For example, a workpiece may experience elevated temperatures while supported by the chuck during a semiconductor processing step. Cooling fluid passing through the chuck's cooling system can be used to remove heat from the workpiece and control the temperature of the workpiece.
[0005] The base of the electrostatic chuck assembly must be made of a high-strength solid material that can be machined to form structures with high-precision features (e.g., size, flatness, surface roughness, complex temperature control channels, and pores). Materials currently used to make the base of the electrostatic chuck include aluminum and other metals or ceramics that can be formed into a precision base structure by machining techniques. With the exception of alumina, these materials can exhibit high hardness properties that make them difficult and expensive to manufacture using high-precision machining techniques.
[0006] By existing methods, to form a base containing internal (enclosed) cooling channels, two opposing pieces are formed by machining in separate parts (eg halves), and the two separately formed pieces are typically joined together by a vacuum brazing step or an electron beam welding step.
[0007] Vacuum brazing is a specialized process for the aviation industry and may be both expensive and difficult to obtain. Vacuum brazing involves forming a bond between two opposing surfaces by using a furnace to melt a "filler material" placed between the two surfaces and allowing the melted filler material to solidify and form a bond or vacuum brazed joint. The filler material may be a material that melts at a temperature lower than the melting temperature of the two pieces that are combined. The joint formed by the "filler" material can usually be detected in a vacuum brazed structure. In general, the combination of forming two separate pieces by complex machining steps and then vacuum brazing steps leads to high material and processing costs and potentially long manufacturing lead times.
[0008] An alternative process uses a formed tube as a placeholder for the cooling channels, followed by casting material over the tube to form the base.
[0009] Obstacles in manufacturing electrostatic chuck bases require further improvements in the materials and manufacturing processes of electrostatic chucks. Summary of the invention
[0010] In one aspect, the present disclosure relates to a suction cup (e.g., an electrostatic suction cup) base, which includes an inorganic composite material, the base including: an upper base surface, which is made of the inorganic composite material; a lower base surface, which is made of the inorganic composite material; an interior, which is between the upper base surface and the lower base surface and is made of the inorganic composite material; and a channel (e.g., a cooling channel) within the interior and is enclosed by the inorganic composite material; the upper base surface, the lower base surface, and the interior include a continuous layer of the inorganic composite material extending from the upper base surface to the lower base surface.
[0011] In another aspect, the present disclosure relates to a method of forming a chuck (e.g., an electrostatic chuck) base by additive manufacturing. The method includes: forming a lower portion comprising a continuous bottom surface by additive manufacturing; forming a middle portion comprising a channel (e.g., a cooling channel) above the lower portion by additive manufacturing; and forming an upper portion comprising a continuous upper surface above the middle portion by additive manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 is a side view of the described electrostatic chuck assembly.
[0013] Figure 2A is a top view of the described base.
[0014] Figure 2B and 2C Show a side cutaway view of the described base.
[0015] Figure 3A The steps of the described example method are shown.
[0016] Figure 3B The steps of the described example method are shown.
[0017] The drawings are schematic, exemplary and not necessarily drawn to scale. DETAILED DESCRIPTION
[0018] The following description relates to methods for preparing solid, substantially non-porous, three-dimensional structures (e.g., base structures used as components of electrostatic chuck assemblies) by additive manufacturing methods. These include methods generally referred to as "3D printing" techniques.
[0019] A chuck, such as an electrostatic chuck, includes a base component that supports various functions of the chuck assembly, including heat dissipation, backside airflow, electrical connections, etc. For advanced applications, the base may also preferably be prepared to exhibit a coefficient of thermal expansion within the range of that of another component of the assembly (the ceramic layer) to improve the thermal performance and planarity of the chuck assembly. Conventional methods of preparing the base component of an electrostatic chuck involve machining techniques that are not easily able to meet some or all of the physical requirements of the base, depending on the material type of the base. For ceramic materials, machining is extremely challenging and forming buried (internal) channels, such as cooling channels, is very difficult.
[0020] Additive manufacturing methods generally involve a series of individual layer forming steps that sequentially form multiple layers of a solidified feedstock composition derived from a feedstock layer. Using a series of additive manufacturing steps, each step forming a single layer of the structure, multiple layers of solidified feedstock are sequentially formed into a structure referred to herein as a multilayer composite material (or "composite material").
[0021] As used herein, the term "composite material" (or "multilayer composite material") refers to a structure formed by additive manufacturing, by sequentially forming a series of multiple individual and individually formed layers of solidified raw materials. The composite material may take the form of a base ("base") of an electrostatic chuck, or may be one or more portions of the base, such as a lower portion and interior of the base. The composite material (i.e., the base structure) including each of the top portion (having a top surface), the bottom portion (having a bottom surface), and the interior portion (e.g., containing cooling channels) may be referred to herein as a "continuous" base or a "continuous layer" of the base, where all three portions are formed and held together exclusively by the layer formation steps of the additive manufacturing process (e.g., without using a vacuum brazing step or any other type of bonding step to bond two separately produced pieces together).
[0022] In this context, the term "continuous" means that the base or layer structure is formed from a plurality of sequentially formed layers into a single composite structure. The formation of the composite structure may be a continuous or uninterrupted process. The term "continuous" does not refer to structures that are prepared by forming two individual pieces separately and then bonding the two separately formed pieces together (e.g., by vacuum brazing techniques or different types of bonding techniques). A continuous base structure is seamless and / or comprises a material that is uniform in composition throughout the base structure. A continuous base does not include seams or boundaries resulting from a bonding step, especially seams or boundaries made of bonding or filler materials having a composition different from that of the material of the base. A continuous base structure does not include a base structure formed by bonding more than one individual component with or without bonding or filler materials, even if the individual components may comprise the same material.
[0023] One specific example of an additive manufacturing technique is a technique generally referred to as "selective laser melting." Selective laser melting (SLM), also known as direct metal laser melting (DMLM) or laser powder bed fusion (LPBF), is a three-dimensional printing method that uses a high power density laser to melt solid particles of feedstock, allowing the molten (liquid) material of the particles to flow to form a continuous layer of molten material, and then allowing the continuous layer to cool and solidify to form a solidified feedstock. According to certain specific example methods, the particles of feedstock may be completely melted to form a liquid (i.e., liquefied), and the liquid material is allowed to flow to form a substantially continuous, substantially non-porous (e.g., greater than 80%, 85%, or 90% porosity) film, which then cools and hardens into a solidified feedstock layer of a multi-layer composite material.
[0024] The selective laser melting method includes features similar to another additive manufacturing technique called selective laser sintering ("SLS"). Selective laser sintering uses laser energy to cause particles of feedstock to become sintered, that is, to melt without melting the particles. This results in a structure formed from the material of the heated particles with spaces between the particles, meaning that the structure is porous. In contrast, selective laser melting can be used to cause particles to become completely melted to form a solid (substantially non-porous) three-dimensional structure.
[0025] The present description relates to forming a base for an electrostatic chuck using additive manufacturing techniques, such as selective laser melting. Additive manufacturing techniques can be a cost-effective technique for forming these base structures, especially compared to previous methods that included complex and difficult machining techniques and steps of separately forming multiple (e.g., two) individual pieces of the base and then bonding the multiple pieces together to form a complete base structure (e.g., by a vacuum brazing step).
[0026] Additive manufacturing techniques may be used to form base structures made of a variety of materials including metallic materials (including alloys) and metal matrix composites. Using additive manufacturing techniques including selective laser melting techniques, the range of viable metals, alloys, and metal matrix composites that may be used to form the base may advantageously include materials that are not easily formed into useful base structures by previous techniques (e.g., machining techniques). The range of materials that may be used for additive manufacturing techniques include metals and metal alloys that can be melted by laser energy, such as aluminum alloys, titanium alloys, and various metal matrix composites, some of which are not easily machined by machining. Example materials may exhibit high hardness, such that the materials may be difficult to machine by machining techniques to form the precision structures of the electrostatic chuck base, including precision dimensions and complex channels (e.g., cooling channels). Using additive manufacturing techniques, these materials may be machined to form base structures including complex enclosed ("buried," "embedded," or defined) channels, even when formed from materials that are difficult to similarly form by using standard machining techniques.
[0027] The material used to prepare the base can be any material used to prepare the base of the electrostatic chuck assembly, such as inorganic materials including various metals (including alloys) and metal-based composite materials. The term "metal" is used herein in a manner consistent with the meaning of the term "metal" within metals, chemistry, and additive manufacturing technology, and refers to any metal or metalloid chemical element or alloy of two or more of these elements.
[0028] The term "metal matrix composite" ("MMC") refers to a composite material manufactured to include at least two components or two phases, one phase being a metal or metal alloy and the other phase being a different metal or another non-metallic material, such as fibers, particles, or whiskers, dispersed throughout a metal matrix. The non-metallic material may be carbon-based, inorganic, ceramic, etc. Some example metal matrix composites are made from the following combinations: aluminum alloy and alumina particles; aluminum alloy and carbon; aluminum alloy and silicon; aluminum alloy and silicon carbide (SiC); titanium alloy and TiB2; titanium alloy and silicon; titanium alloy and silicon carbide (SiC).
[0029] Metals and metal alloys that can be used according to the methods described herein include metals and metal alloys that have been used in the past to prepare base structures for electrostatic chuck assemblies, and additionally include other materials that have not been used. Useful or preferred materials include metals such as iron alloys (such as stainless steel and other types of steel), titanium and titanium alloys, aluminum and aluminum alloys, and various metal matrix composite materials.
[0030] According to the present method, the pedestal can be made from a wider variety of materials than can be used when the pedestal is made by previous methods (e.g., machining methods). Because a wider variety of materials can be used, the material of the pedestal can be selected to provide physical properties that are particularly useful or desirable in a pedestal for an electrostatic chuck assembly and in view of the materials used for other components of the assembly (e.g., adjacent ceramic layers).
[0031] The coefficient of thermal expansion ("CTE") is a known physical property of metals, metal matrix composites, and ceramic materials. The materials of the layers in the described pedestals may generally have coefficients of thermal expansion comparable to those of various metals and ceramic materials that have been previously used to form components of pedestal assemblies for electrostatic chucks. Some example materials that may be used as pedestals or ceramic layers of the described pedestal assemblies and their approximate CTE values are as follows: Alumina (8.1×10 -6 m / (m K)), aluminum (21 to 24×10 -6 m / (m K)), aluminum alloy (AlSi7Mg) (21 to 22×10 -6 m / (m K)), aluminum nitride (5.3×10 -6 m / (m K)), stainless steel 440C (10.2×10 -6 m / (m K)), stainless steel 17-4PH (10.8×10 -6 m / (m K)), steel M2 (tool) (11×10 -6 m / (mK)), titanium (8.6×10 -6 m / (m K)), titanium alloy Ti-6Al-4v (TC4) (8.7 to 9.1×10 -6 m / (m K)).
[0032] In exemplary terms, useful or preferred coefficients of thermal expansion of the metal or metal matrix composite material used to prepare the described base may range from 4×10 -6 m / (m K) to 30×10 -6 m / (m K), for example, from 5×10 -6 m / (m K) to 25×10 -6 m / (m K).
[0033] In certain preferred pedestal structures and electrostatic chuck assemblies, the material of the pedestal may preferably be a material having a coefficient of thermal expansion that matches or is similar to that of an adjacent layer of the assembly. Typically, as part of an electrostatic chuck assembly, the pedestal layer is located near, adjacent, or otherwise sufficiently close to a ceramic layer of the assembly so that the pedestal layer and the ceramic layer experience similar temperature conditions and the thermal expansion of one is affected (e.g., constrained) by the other. If so, a useful combination of a pedestal layer and a ceramic layer of the assembly may be made of materials having substantially equal coefficients of thermal expansion. A preferred pedestal for an electrostatic chuck assembly may have a coefficient of thermal expansion comparable to that of a ceramic layer that is part of the same chuck assembly. The coefficient of thermal expansion of the pedestal may be within 25%, 20%, 15%, 10%, or 5% of the coefficient of thermal expansion (m / (m-degrees Kelvin)) of the ceramic layer.
[0034] The layer-by-layer approach of the described additive manufacturing techniques can allow for the formation of complex, precise and composite shapes that are efficient structures contained in the electrostatic chuck base. Relative to mechanical machining techniques, the described additive manufacturing techniques can more efficiently produce patterns (e.g., channels) that are highly complex, cover a large portion of the surface area of the base, occupy a large volume of the base structure out of the total volume of the base structure, have various cross-sectional shapes, or specially designed (custom) patterns. These patterns can be voids, openings, indentations, cavities, channels, cutouts of shapes designed for various functions. These functions include heating, cooling, reducing weight, enhancing mechanical properties, providing stability of the support surface, and other possible functions. In one example, the pattern is a channel for cooling, wherein a coolant is allowed to flow through the channel to remove heat from the chuck and the workpiece supported thereon.
[0035] The channels formed by the additive manufacturing technique may have different or various shapes (cross-sections), patterns (relative to the surface of the base assembly) and sizes (e.g., width or diameter of the channel), arrangements (relative position of the channel), and may have surface features that allow fluid to flow smoothly and efficiently through the channel. For example, while the machining step typically produces a square channel (cross-section), the additive manufacturing technique may be used to produce a circular channel (cross-section), which may allow improved (laminar) flow through the channel than turbulent flow through a channel with a square cross-section. As another example, the channel may be formed to exhibit an asymmetric cross-section, which may allow the design of a channel with improved heat transfer efficiency through the base surface. In another example, the additive manufacturing technique may form two or more channels interconnected therebetween. The two or more channels include various cross-sectional shapes. In another example, the two or more channels may have cross-sectional shapes that are different from each other.
[0036] Yet another optional feature of the channels formed as described may be a channel pattern relative to the (typically circular) surface area of the base and base assembly that is designed to improve heat transfer efficiency relative to a particular workpiece and the non-uniform features of a particular workpiece that may be supported by the base assembly. This feature is sometimes referred to as "conformal cooling" and allows the channel pattern within the base to be designed and formed in a specific design to match the specific heat dissipation requirements of the workpiece (e.g., semiconductor or microelectronic device or wafer) that will be supported by the electrostatic chuck assembly during use. Additionally, additive manufacturing techniques allow for less complex manufacturing methods for forming the base, including manufacturing methods with fewer overall steps, compared to previous methods of forming two separate base pieces and using a vacuum brazing step to join the two pieces. With additive manufacturing, a complete (or substantially complete) functional base layer of the electrostatic chuck can be prepared using a single manufacturing process (a single additive manufacturing "step"), which provides high manufacturing efficiency (high throughput) with a reduced amount of time per unit. A base layer complete with substantially all desired structures (including the bottom, interior, and top) can be prepared by a single series of additive manufacturing steps. For example, a so-called "one-step" additive manufacturing process for forming the base structure may form many, most, or all of the desired structures of the base (including the bottom, interior, and top) as a single continuous layer, as the described multi-layer composite material. The one-step additive manufacturing process avoids the need to separately form multiple separate pieces by separate steps, followed by the additional step of bonding the multiple separately formed pieces together to form a functional base structure.
[0037] In addition, additive manufacturing techniques can be used to form bases with high precision dimensions. For example, the base has a dimensional accuracy within + / -0.13 mm; the base has a positioning (or location) accuracy within + / -0.13 mm; the perpendicularity is within + / -0.01 mm; the flatness is within + / -0.04 mm; the parallelism is less than 0.05 mm; the angular accuracy is within + / -0.5°; and / or the leakage rate of closed features (such as channels) is less than 10 -10 mbar L / s.
[0038] According to example methods, a pedestal may be prepared to exhibit a high level of flatness (e.g., an "ultra-flat" surface), and the high level of flatness of the pedestal may improve the level of flatness of the electrostatic chuck assembly, where the flatness is measured at the upper surface of the metal matrix composite material layer of the assembly. Flatness is a typical property of an electrostatic chuck or a pedestal component of a chuck, and may be measured by known techniques, such as by using a coordinate measuring machine. In general, flatness is measured and reported as the height difference (in the z-direction) between the peaks (highest measurement points) and the troughs (lowest measurement points) of the measured surface, and is given in distance units (e.g., microns). A pedestal having a diameter of 300 millimeters prepared by only a machining step may be formed to exhibit a flatness as low as 30 microns. For the surface of a similar pedestal (300 millimeter diameter) described herein, the flatness of the pedestal may be improved relative to a pedestal formed exclusively by machining, forming the pedestal by an additive manufacturing step, and then further machining the pedestal surface by a machining step. The flatness of the pedestal surface after additive manufacturing may be less than 45 or 50 microns, for example, may be as low as 40 microns. The surface may be further processed by a machining step such as grinding or polishing to provide a lower flatness, such as a flatness of less than 30 microns, such as less than 20 microns or down to about 15 microns.
[0039] For certain advanced applications of electrostatic chuck assemblies (e.g., low temperature, low angle implantation), a useful chuck assembly should exhibit ultra-high flatness measured at the upper surface of the assembly (e.g., at the top of the ceramic layer). For a 300 mm chuck, preferred flatness values for certain applications of the chuck assembly may be below 10 microns, measured at the upper ceramic surface. It is also important to maintain this ultra-high flatness property over a wide operating temperature range. The flatness level of the chuck assembly over a temperature range can be improved by closely matching the thermal expansion coefficient values of the different layers of the chuck assembly (ceramic layer and base layer), also improving heat dissipation from the assembly (heat removal by fluid flow through the base) to extract heat, and also improving the flatness of the surfaces of these layers at the junctions between the layers. Materials used to form the base of the chuck assembly (e.g., titanium, titanium alloys, and metal matrix composites) can result in improved CTE matching and improved flatness relative to previous materials commonly used to form chuck bases (e.g., aluminum, which is not as stiff as these materials).
[0040] In addition, example methods of the present disclosure can be used to prepare a base to exhibit relatively low roughness. Roughness is a typical property of a base of an electrostatic chuck and can be measured by known analytical techniques, including being represented by the arithmetic mean of a surface roughness profile (denoted as "Ra"), for example, by using a 3D laser microscope or a needle profilometer. Ra is calculated as the roughness average of the microscope peaks and valleys measured on the surface. Example surfaces of bases prepared by the described additive manufacturing method followed by a mechanical processing step to reduce the roughness of the surface prepared by the additive manufacturing method can have a surface roughness (Ra) of less than 1 micron, such as less than 0.5 microns or as low as about 0.1 microns. Roughness (Ra) can be determined by one of various standard methods, such as by ISO 4287-1:1984 or ASTM F 1048. Improved precision formation of the base allows for improved, more precision formation of a chuck assembly including a ceramic layer attached to the base, including improved flatness measured at the top of the ceramic layer. A typical pedestal prepared by machining methods and having a diameter of 300 millimeters can be combined with a ceramic layer to form an assembly that exhibits a flatness as low as 30 microns measured at the upper ceramic surface. In an example embodiment, a pedestal layer of the present description can be combined with a similar ceramic layer to form an assembly having a diameter of 300 millimeters that exhibits a flatness measured at the upper ceramic surface of less than 30 microns, such as a flatness of less than 25 microns, such as less than 20 microns or down to about 15 or 10 microns. In order to achieve this low level of flatness of the metal matrix composite layer of the pedestal assembly, the pedestal layer can be formed by additive manufacturing, and the surface of the pedestal assembly (which will contact the metal matrix composite layer) can be machined to improve the flatness of the surface produced by the additive manufacturing step.
[0041] Additional processes may be employed after the additive manufacturing process. For example, a de-powdering process may be performed to remove loose powder generated as a byproduct during the additive manufacturing process. The de-powdering process removes loose powder from the surface of the suction cup or channel through an ultrasonic vibration-assisted vacuum system, followed by blowing compressed air from the channel inlet to carry away the loose powder. In another example, the additional process may include a cleaning process to remove contamination, such as oil or grease, on the suction cup induced during the additive manufacturing process. In another example, a heat treatment may be used to alleviate thermal stress induced during the additive manufacturing process.
[0042] The methods described herein use additive manufacturing techniques to form a base structure (e.g., a continuous base layer or a portion of a base layer) by sequentially forming multiple layers of a composite material. The composite material is formed from: multiple layers, each of which can individually have any useful thickness; and one or more materials that can be melted to flow and form a dense inorganic (e.g., metal or metal matrix composite) solid that serves as a substantially non-porous material for the base structure.
[0043] Generally, the base can be considered to have a flat and thin profile, usually a circular structure (when viewed from top and bottom), such as a flat disk comprising two relatively flat and circular surfaces and a thickness therebetween. The two relatively surfaces serve as the top and bottom of the base layer. The interior of the base exists between the two relatively surfaces. The interior may include a system of closed channels (e.g., cooling channels) that extend through the interior in a winding, tortuous, twisting, circuitous, or serpentine path.
[0044] The channels can accommodate a flow of fluid (e.g., water or another liquid or gaseous fluid) that can be used to control the temperature of the base during operation of the base. Other structures can also be formed into the surface of the base, such as vertical openings ("pores") extending between the thickness and between two opposing surfaces of the base (from top to bottom and throughout the thickness) or channels or grooves at one or both of the top and bottom surfaces.
[0045] The functional base layer of the suction cup assembly can be considered to include at least three different parts: a lower part, which includes a bottom surface; an upper part, which includes an upper surface opposite the bottom surface; and a middle part ("interior"), which is disposed between the upper and lower parts and may contain channels (e.g., cooling channels). Preferably, according to the preferred method described, all three parts and all of their layers can be produced by an additive manufacturing method, by which a single (preferably, uninterrupted) series of layer forming steps (optionally and preferably, wherein all layer forming steps are performed on a single additive manufacturing device) is used to form all layers of the functional base layer as a continuous seamless layer of inorganic material, which does not include any seams or internal boundaries, such as seams or boundaries that can be formed by a bonding step (e.g., vacuum brazing). "Uninterrupted" means that each layer forming step in the series of additive manufacturing steps is performed sequentially, no different type of steps (e.g., any type of non-layer forming steps) are performed between any two of the layer forming steps, and there is no bonding step (other than the additive manufacturing step) that uses a filler material, a brazing material, an adhesive material, etc. to bond two pieces of the base layer together.
[0046] As an example of the currently described method, the method may include: forming a lower portion of the base including a bottom surface by additive manufacturing; forming a middle portion of the base including a cooling channel above the lower portion by additive manufacturing; and forming an upper portion of the base including an upper surface above the middle portion by additive manufacturing.
[0047] Each layer of the composite material can be formed of a desired material and have a desired thickness as needed to produce a base layer in the form of a multilayer composite material with desired properties. Through an exemplary additive manufacturing method, each layer is prepared from a collection of particles (referred to as "feedstock"), usually in powder form. The feedstock contains small particles made of one or more different inorganic materials, which can be melted by a high-energy laser to liquefy and flow to form a continuous layer of molten material, which is then cooled and solidified to form a layer of the multilayer composite material.
[0048] The particles that can be used according to the present description can be any particles that can be processed to form the useful multilayer composite materials described. The particles can be included in the feedstock in powder form, including, consisting of, or consisting essentially of inorganic particles that can be melted using energy from a high energy laser to form layers of the multilayer composite material.
[0049] Examples of useful particles include inorganic particles that can be melted or liquefied by laser energy to form the layers of the described base structure. Examples of such particles include inorganic particles made of metals (including alloys) and metal-based composite materials. Some useful examples generally include metals and metal alloys (such as aluminum, titanium and alloys thereof) and metal-based composite materials. A specific example of a useful aluminum alloy is AlSiMg. A specific example of a useful titanium alloy is Ti6Al4V.
[0050] Useful particles of the feedstock can have any effective size (e.g., average particle size) or size range, including micron-sized or relatively small particles (e.g., having an average size of less than 500 microns, less than 100 microns, less than 50 microns, 10 microns, or less than 5 microns).
[0051] The particles may be selected to achieve the effectiveness of the described processing to be able to be contained in a feedstock, formed into a layer of the feedstock, and melt flow to form a continuous layer that can be cooled to form a solidified feedstock as a layer of a multi-layer composite material. The size, shape, and chemical composition of the particles may be any effective for these purposes.
[0052] The particles may be in the form of a raw material composition that can be used in the additive manufacturing process of the present description. According to an example, the raw material used in the additive manufacturing process may contain particles that can be melted to form a continuous, substantially non-porous layer of a multilayer composite material. The raw material need not contain any other materials, but may optionally contain a small amount of other materials as required. The example raw material composition may contain inorganic particles that account for at least 80, 90 or 95, 98 or 99 weight % of the total weight of the raw material composition. Other ingredients may be present in small amounts, such as one or more of a flow aid, a surfactant, a lubricant, a leveling agent, etc., as required.
[0053] Each layer of the multilayer composite material can be formed to have any useful thickness. The thickness of the layer of the multilayer composite material is measured after the layer of the composite material is formed by melting the particles of the raw material layer to form a continuous, melted and then solidified layer of the composite material. The example thickness of the layer of the composite material can be in the range of from 30 microns to 100, 200 or more microns, for example, from 30 to 50, 60, 70, 80 microns until 90, 100, 150, 200, 300, 400 or 500 microns. In an example composite structure, all layers of the composite material can have the same thickness or substantially the same thickness. In other example composite structures, the layers may not all have the same thickness, but different layers of the composite material may each have different thicknesses.
[0054] According to certain example methods and base structures of the present description, a base can be prepared by an additive manufacturing step by forming layers of composite material having different thicknesses at different portions of the base. Examples of these methods and structures involve: forming one or more layers having a relatively low thickness (referred to as "fine layers"), such as at the top and bottom of the base; and forming a layer having a relatively high thickness ("rough layer"), such as at the inner portion (or middle portion) of the base between the top and bottom. Alternatively, the middle portion may include a fine layer, while the upper portion and the bottom portion include a rough layer.
[0055] As part of a multilayer composite material (e.g., in the form of a base layer), the position of one or more fine layers relative to the rough layer can be any useful position. Various positions of the rough layer and fine layer of the composite material and various orders of forming the rough layer relative to the fine layer can be effective. However, according to specific embodiments of the described base structure and related methods, one or more fine layers may preferably be present at one or more surfaces of the base, while the rough layer may be present at the interior of the same base. In other words, the fine layers and the rough layers may be formed alternately. The fine layer may be desirably located at one or more surfaces because the fine layer may exhibit more desirable physical properties relative to the rough layer (see below). The layers of the interior of the base (whose higher quality is less important) may be prepared from the rough layer to improve manufacturing efficiency (see below).
[0056] Forming the layers of the base to have different thicknesses can produce advantages in terms of processing efficiency and the physical properties of the base (or portion of the base). Forming one or more "rough" layers of greater thickness will have the beneficial effect of increasing the productivity and efficiency of the base. The thicker rough layers may have a reduced quality relative to the thinner (fine) layers (see below), but forming the layers of relatively greater thickness will increase the productivity of the base (reduce the amount of time required); the increased thickness of the thicker (rough) layers will reduce the total number of layers that must be formed and the number of layer formation steps required to produce a base of a particular thickness. The thickness of the rough layer may be a thickness within the typical range of layers formed by additive manufacturing methods, such as a thickness in the range from 70, 80, 90 or 100 microns up to 500 microns. The greater thickness of the rough layer will reduce the number of steps and the amount of time required to form a completed multilayer composite material of a predetermined total thickness.
[0057] When the layer formation steps use the same raw material and the same laser, the thickness of the layer formed by the additive manufacturing technique can affect the physical properties (quality) of the layer. For example, a thinner layer can be formed to contain fewer internal open spaces or "holes" than a thicker layer formed using the same raw material and the same laser. The presence of holes in the layer can be measured and represented by the apparent density of the layer. In general, when using an additive manufacturing process that applies the same laser and the same laser power to the raw material layer, the apparent density of the thicker (rougher) layer will be lower than the apparent density of a similar (e.g., fine) layer having a lower thickness but made from the same raw material in the same amount of time.
[0058] Apparent density refers to the measured density of a layer of a composite material relative to the actual (or theoretical) density of the material used to form the layer in a 100% solid, non-porous (zero porosity) form. The layer of the composite material will typically be a continuous solid material because it is formed by the steps of melting particles of a feedstock and allowing the molten particles to flow and form a continuous layer (e.g., a "film") from the material of the liquefied particles. However, typically, the continuous solid material formed is not 100% solid, but contains a small amount of void space or pores that are not removed during the layer formation process. The pores can cause the performance of the base to be reduced by potentially allowing fluids (e.g., cooling water) to leak from the porous material of the base through the channel to the outside of the base (especially when the base is used in a process under vacuum).
[0059] Typically, the pores in a layer or composite material may be optically visible at the surface or interior of the composite material with or without magnification. Alternatively, these void spaces may be detected as a reduced density (apparent density) of a layer or portion of a composite material. A layer without void spaces formed therein (100% solid inorganic material with 0% pores) will have a density equal to the density of the inorganic material (no pores) used to prepare the layer. A large amount of inorganic material containing pores will have a density (apparent density) slightly lower than the density of the inorganic material.
[0060] The density of a layer (apparent density, when pore volume is included in the layer) is a measure of the mass of the layer divided by the volume of the layer (including pore volume) divided by the actual (theoretical) density value of the material used to form the layer with zero pore volume, and is reported as a percentage of the actual density. The apparent density value of a layer or a portion of the described composite material (or base layer) can generally be relatively high, for example greater than 80%, 90%, 92%, 96%, 98% or 99% of the actual density of the material used to form the layer.
[0061] When a layer of a composite material is formed from inorganic particles, the energy from a high-power laser is used to melt the inorganic particles formed as a raw material layer. The molten particles flow to form a continuous layer (e.g., a "film") that solidifies into a composite material layer. Ideally (theoretically), the laser energy will completely melt all particles of the raw material composition used to prepare the layer, and the flow of the liquefied particulate material will form a void-free liquid layer that solidifies to form a void-free solid. However, in practice, the layer formed in this way may generally contain defects, voids, or partially unmelted particles, and the number of these defects is larger for layers formed to have a larger thickness (for the same raw material, using the same laser, and exposing the laser to the same time of the raw material layer area).
[0062] The steps of forming a rough layer of the composite material will include forming a raw material layer with a higher thickness and melting particles of the raw material. Using the same amount of laser power for the rough layer (with more particles) as can be used to melt particles of the fine layer (with fewer particles) and the same time of exposing the laser to the raw material area, the laser power per particle used to melt the number of particles of the thicker raw material layer (with more particles) is lower. The lower received laser energy per particle of the raw material layer (which is more particles for the rough raw material layer) can cause the rough layer to have a higher defect level than the fine layer.
[0063] A higher amount of defects may be associated with a lower apparent density. When the same feedstock, the same laser, and the same time of exposing the laser to the feedstock layer area is used, the apparent density of the rough layer will generally be lower than the apparent density of the fine layer. In the example methods and base structures, the apparent density of any layer of the base may preferably be at least 98% or 99%. More particularly, the apparent density of the rough layer of the base may preferably be at least 99.0%, such as at least 99.2% or 99.4%. The apparent density of the fine layer of the base may preferably be greater than the apparent density of the rough layer of the same base, and may be at least 99.4%, such as at least 99.6%.
[0064] Forming one or more "fine" layers with reduced layer thickness can be used to improve the physical quality of the base structure. It has been found that finer layers of composite materials produced by additive manufacturing methods exhibit useful or preferred physical properties, such as higher density and relatively few defects, such as holes formed in the layer.
[0065] On the other hand, forming multiple fine layers with lower thickness during the additive manufacturing process will reduce the productivity of the multilayer composite material, that is, it will increase the number of steps and the amount of time required to produce a multilayer composite material with a specific thickness because more fine (thinner) layers must be formed, which means that more additive manufacturing steps are required to build a multilayer composite material of a given thickness.
[0066] The thickness of the fine layer may be a thickness within the typical thickness range of layers formed by additive manufacturing methods, particularly at the low end of the range, for example a thickness in the range from 30 to 100 microns, for example from 30 to 50, 60, 70, 80 or 90 microns.
[0067] The described electrostatic chuck is a multi-piece (or "multi-component") structure that includes multiple components assembled together in layers to form an electrostatic chuck assembly. The assembly includes various structures and features that are typical of an electrostatic chuck assembly and that allow the chuck to support a workpiece (e.g., a semiconductor substrate, a microelectronic device, a semiconductor wafer, precursors thereof) during processing with electrostatic attraction that holds the workpiece in place at an upper surface ("workpiece contact surface") of the chuck. Example workpieces used with the electrostatic chuck include semiconductor wafers, flat panel displays, solar cells, photoreticles, photomasks, etc. The workpiece may have an area equal to or greater than the area of a circular 100 mm diameter wafer, a 200 mm diameter wafer, a 300 mm diameter wafer, or a 450 mm diameter wafer.
[0068] The chuck includes an upper "workpiece contact surface" adapted to support a workpiece during machining. The upper surface typically has a circular surface area with a circular edge defining the perimeter of both the workpiece contact surface and the multilayer chuck. As used herein, the term "workpiece contact surface" refers to the upper exposed surface of the electrostatic chuck that contacts the workpiece during use and includes a "main field" made of a ceramic material and having an upper surface, typically with a relief at the upper surface, and with an optional conductive coating that may cover at least a portion of the upper surface. The workpiece is held at the workpiece contact surface, in contact with the upper surface of the relief, over the upper surface of the ceramic material, and held against or "clamped" to the electrostatic chuck during use of the electrostatic chuck. The example electrostatic chuck assembly can be used with AC and DC Coulombic chucks and Johnsen-Rahbek chucks. In the present embodiment, the upper "workpiece contact surface" is formed by depositing a fine layer of a composite material using an additive manufacturing method.
[0069] The chuck assembly (or simply "chuck") also includes many other layers, devices, structures and features that are required or optional for the operation of the chuck. These include: an electrode layer that creates an electrostatic attraction between the chuck and the workpiece to hold the workpiece in place during processing; a grounding device, such as a ground layer and related electrical connections; a measurement device for measuring pressure, temperature or electrical properties during the processing step; an airflow conduit as part of the temperature control function; a backside airflow function for airflow and pressure control between the workpiece contact surface and the workpiece; a conductive surface coating; and others.
[0070] One layer of a typical chuck assembly is a ceramic layer (also referred to as a dielectric layer) at the top of the assembly. The ceramic layer may be the top layer of the assembly and may include the upper surface of the chuck, rather than a conductive coating, relief, etc. placed on the upper surface of the ceramic layer. The conductive coating at the upper surface may be connected to electrical ground via a grounding layer, grounding pin, etc. also included in the chuck assembly. The ceramic layer may be made of useful ceramic materials, such as aluminum oxide, aluminum nitride, quartz, SiO2 (glass), etc. As desired, the ceramic layer may be made of a single (monolithic) material layer, or may alternatively be made of two or more different materials, such as multiple layers of different materials. The total thickness of the ceramic layer (having one or more ceramic material layers) may be any effective thickness, such as a thickness in the range of from 1 to 10 millimeters, such as from 1 to 5 millimeters.
[0071] The ceramic layer is supported by an underlying base layer (referred to as "base"), which may be made of metal, such as aluminum, aluminum alloys, titanium, titanium alloys, stainless steel, metal matrix composites, etc., as described herein.
[0072] One or more of the following is typically between the ceramic layer and the base: a bonding layer (such as a polymeric adhesive), an electrode, a ground layer, an insulating layer to allow the electrodes and other layers to function electrically, or additional circuitry.
[0073] Figure 1 An example of a useful suction cup assembly is shown in FIG. Suction cup assembly 10 includes a base 12, a ceramic layer (assembly) 14, and a bonding layer 16 that bonds the base 12 to the ceramic layer 14. The ceramic layer 14 includes subcomponents such as electrodes. A relief pattern 18 is at the upper surface of the ceramic layer 14. As illustrated, a wafer 20 is supported by the relief. A space 22 exists between the lower surface of the wafer 20 and the upper surface of the ceramic layer 14. The space 22 is created by the relief 18 located at the upper surface of the ceramic layer 14, which supports the wafer 20 at a distance slightly above the upper surface of the ceramic layer 14. During use, a gas flow (e.g., a cooling gas) can pass through the space 22 between the wafer 20 and the ceramic layer 14 to control (e.g., reduce) the temperature of the wafer 20. The base 12 contains cooling channels (e.g., cooling channels) that are not specifically illustrated.
[0074] The suction cup assembly of the present description includes a base component, which includes channels (e.g., cooling channels). According to the method as described herein, the entire structure of the base and the internal channels is produced using additive manufacturing technology (e.g., selective laser melting technology). The channel system can be formed in the base during the additive manufacturing of the base as an open space pattern (e.g., "void" space) that forms connecting channels distributed within the multilayer composite material formed to the base structure, that is, the channel is defined by the lack of multilayer composite materials at the channel location, and no other structure is required to form or define the structure of the channel. The channel runs through the interior of the base layer and does not require a structure or surface other than the channel space formed in the base layer during the formation of the base by the additive manufacturing method. The channels can be interconnected with each other. The channels are defined by the surface of the multilayer composite material, without other materials. Specifically, the channel does not contain additional structures other than the structure of the multilayer composite material, such as separate tubes, pipes, or conduits formed separately from the composite material and placed in the composite base layer. In use, a fluid, which may be a gas or a liquid, flows through the channel in contact with the sidewalls of the channel made of the multilayer composite material, and there is no other material to form or define the inner surface of the channel.
[0075] The channel (e.g., cooling channel) is used to circulate a fluid (e.g., water or another liquid for heat exchange) through the interior of the base to control the temperature of the base. The channel is formed at the interior of the base and extends in a horizontal direction relative to the area of the base when viewed vertically (e.g., from above, from a "top-down perspective"). Alternatively, the channel may extend in a direction other than the horizontal direction (e.g., a vertical direction). The channel includes at least one inlet in the base that allows fluid to enter the base and at least one outlet that allows fluid to leave the base.
[0076] The channels (e.g., cooling channels) or portions thereof (which are part of the base) may be located at any useful location within the base and in any useful pattern relative to the area of the base. Advantageously, the channels of the described base may be formed in the base to provide improved performance (heat exchange, e.g., cooling) relative to channels formed by machining techniques. Channels formed by additive manufacturing techniques may be more precise, may be formed with alternative cross-sectional shapes (which cannot be formed by machining), may form more complex (serpentine) patterns, and may be formed in the base at a higher channel density relative to channels formed by machining (meaning that the percentage of the channels in the total volume of the base structure is greater than channels formed by machining). Examples of cross-sectional shapes of the channels include circular, triangular, hexagonal, dome-shaped (curved at one end and flat at the opposite end), and teardrop-shaped shapes. The cross-sectional shape of the channel is achieved by the additive manufacturing process described above.
[0077] Figure 2A and 2BA single example of a base 100 of the present description is illustrated. The base 100 includes a perimeter 110, an upper surface 102, a lower surface 104, and a thickness between the two opposing surfaces. A cooling channel 106 (shown as having a circular cross-section) is presented as a serpentine pattern at the interior of the base.
[0078] Figure 2C Examples of cross-sectional shapes of different cooling channels are shown, including triangular (i), hexagonal (ii), dome-shaped (curved at one end and flat at the opposite end) (iii), and teardrop-shaped (iv) cross-sections.
[0079] In these or other cross-sectional shapes, other features of channels (e.g., cooling channels) may also be incorporated into the base design that are not possible or easily achieved using machining techniques. For example, the channel may be formed to have a larger volume near the top surface of the base than the bottom surface of the base; the channel may be shaped to have a larger portion of the channel near the top surface, or the channel may be located closer to the top surface and farther from the bottom surface. Alternatively or in addition, the heat exchange circuit may be located at different levels of the thickness of the base rather than at a single level of the thickness of the base; some portions of the heat exchange circuit may be located at different thickness levels (closer or farther from the top surface) than other portions. Alternatively or in addition, the cross-section of the channel may vary based on the location within the base; the cross-section may be smaller in size (cross-sectional area) or differently shaped at a portion of the base near the center of the base, and larger or differently shaped at the edge (or vice versa) to allow for more uniform heat transfer.
[0080] The described base can be prepared by an additive manufacturing method using a series of individual layer forming steps to form a dense metal or metal matrix composite multilayer composite structure. As an example, a technology called selective laser melting (SLM) is a version of an additive manufacturing technology that can be used to form multilayer composite materials in a layer-by-layer manner. Selective laser melting uses high power laser energy to selectively cause metal or metal matrix composite particles of a feedstock layer to melt, flow and form a substantially continuous solidified feedstock layer.
[0081] More specifically, a multilayer composite material can be constructed by sequential steps that produce many thin sections ("solidified raw materials" of a "layer" herein) of a larger three-dimensional structure (composite material). A layer of raw material is formed and includes many particles of a metal or metal-based composite material. Laser energy is selectively applied to the layer of raw material above a portion of the layer of raw material. The laser energy melts the particles at the portion of the raw material exposed to the laser energy. The molten particles liquefy and flow into a continuous material layer of the molten particles and then cool and solidify into a layer of solidified raw material. After forming an initial layer of solidified raw material, an additional thin layer of raw material is deposited above the top surface of the finished layer containing the solidified raw material. The process is repeated to form multiple layers of solidified raw material, each layer formed on top of the previous layer and adhered to the top surface of the previous layer. Multiple layers are sequentially deposited on each finished layer to form a multilayer composite material, which is a composite material of each layer of solidified raw material. Multiple layers may have the same composition and thickness, or may have different compositions and different layer thicknesses.
[0082] Figure 3A An example of a selective laser melting additive manufacturing technique (200) for preparing the described multi-layer composite material is shown in FIG. The process can be performed using commercially available selective laser melting additive manufacturing equipment and particles to form a feedstock. The feedstock 202 is a powder containing a collection of inorganic particles. According to Figure 3A In the example steps shown in FIG. 1 , a powder feedstock (202) contained by a selective laser melting additive manufacturing apparatus is formed into a uniform layer (204, 206) on a building plate of the apparatus. In a subsequent step (208), an electromagnetic radiation source (e.g., a high-power laser) selectively irradiates a portion of this first feedstock layer with radiation of a wavelength and energy that will melt the particles. The molten particles flow into a continuous film and then solidify by cooling. The feedstock layer can be a fine layer or a rough layer and can have any useful thickness. The solidified material of the molten particles forms a solidified feedstock at the irradiated portion. The portion of the feedstock layer that is not formed into a solidified feedstock remains as the original liquid feedstock.
[0083] The build plate moves downward (210) and a second layer (fine layer or coarse layer) of powder feedstock is formed (212) as a second uniform layer above the first feedstock layer and above the solidified feedstock of the first feedstock layer. Then, the electromagnetic radiation source selectively irradiates a portion of the second layer (214), which causes the particles at the portion to melt. Then, the melted portion cools to form solidified feedstock at the portion of the second layer. The portion of the second layer that is not formed as solidified feedstock remains as the original powder feedstock. Steps 212, 214, and 216 are repeated (218) to form a complete multi-layer solidified feedstock composite material surrounded by the original liquid feedstock (202).
[0084] The multi-layered solidified raw material composite is a body of solidified raw material containing each formed layer, and is composed of a plurality of successive layers of material made of melted particles of the raw material. The original raw material (202) can be removed and separated (218) from the multi-layered composite.
[0085] refer to Figure 3B , an example process can be performed using a commercially available selective laser melting additive manufacturing apparatus (230) and using a powder feedstock (232) according to the present description. According to the example steps of the method, the feedstock (232) is formed as a uniform layer of feedstock (234) above a build plate (238) of the apparatus (230). A laser (236) applies electromagnetic radiation (233) to a portion of the first layer (234), which causes the feedstock particles to melt and flow into a continuous layer, which is then allowed to cool to form a first solidified feedstock (240) at a portion. The portion of the feedstock layer (234) that is not formed into solidified feedstock (240) remains as the original feedstock (232). The build plate (238) moves downward (214) and forms a second or subsequent layer of feedstock (242) above the first layer (234) and the first solidified feedstock (240). Next, the laser (236) selectively applies electromagnetic radiation (233) to portions of the second layer (242) to cause the feedstock particles to melt and flow to form a continuous layer, which is allowed to cool and form a solidified feedstock from the second layer. The portion of the second layer that is not formed into the solidified feedstock remains as the original powder feedstock. The sequence is repeated (250) to form a complete multi-layer solidified feedstock composite (252) surrounded by the original feedstock (232). The multi-layer solidified feedstock composite (252) is the body of solidified feedstock containing each molded layer and is composed of the material of the molten particles of the feedstock. The original feedstock (232) can be removed and separated from the multi-layer composite (252).
Claims
1. A suction cup base, comprising: The upper part, which is made of inorganic composite materials, a lower part, which is made of said inorganic composite material, an inner portion, which is located between the upper portion and the lower portion and is made of the inorganic composite material, and a channel located within the inner portion and formed of the inorganic composite material, the upper portion, the lower portion, and the inner portion comprising a continuous layer of the inorganic composite material extending from the upper portion to the lower portion, wherein one of the upper portion and the lower portion includes at least one fine layer having a fine layer thickness, and the inner portion includes at least one rough layer having a rough layer thickness, and wherein the rough layer thickness is greater than the fine layer thickness.
2. The suction cup mount of claim 1, wherein the continuous layer of the inorganic composite material is seamless, and wherein the inorganic composite material is homogeneous in composition.
3. The suction cup mount of claim 1 or 2, wherein the channel has a cross-section selected from circular, triangular, dome-shaped, hexagonal or teardrop-shaped.
4. The chuck mount of claim 1 or 2, wherein at least one of the upper portion and the lower portion has a surface roughness of less than 50 microns.
5. The suction cup mount of claim 1 or 2, wherein at least one of the upper portion, the lower portion, or the interior portion of the suction cup mount has a density of at least 99.6%.
6. A method of forming a suction cup base by additive manufacturing, the method comprising: forming a lower portion of the suction cup base including a continuous bottom surface by additive manufacturing, forming a middle portion of the suction cup base including a cooling channel above the lower portion of the suction cup base by additive manufacturing, forming an upper portion of the suction cup base including a continuous upper surface above the middle portion of the suction cup base by additive manufacturing, Forming the lower portion of the chuck base by additive manufacturing includes forming a plurality of first fine layers, each first fine layer having a first fine layer thickness, Forming the middle portion of the suction cup base by additive manufacturing includes forming a plurality of rough layers, each rough layer having a rough layer thickness greater than a thickness of the fine layer, and Forming the upper portion of the chuck base by additive manufacturing includes forming a plurality of second fine layers, each second fine layer having a second fine layer thickness.
7. The method according to claim 6, wherein Each of the first fine layer thickness and the second fine layer thickness is less than 40 micrometers, and The thickness of the rough layer is greater than 60 microns.
8. The method according to claim 6 or 7, wherein: At least one of the suction cup base surfaces has a surface roughness of less than 50 microns, at least the upper portion of the suction cup base or the lower portion of the suction cup base has an apparent density of at least 99.6%, or Both.
9. The method of claim 6 or 7, wherein the lower portion of the suction cup base, the middle portion of the suction cup base, and the upper portion of the suction cup base are seamlessly formed in one continuous additive manufacturing process using a composite material.
Citation Information
Patent Citations
Sucker base
CN217239427U
Chuck for plasma processing chamber
WO2020185467A1